On the management of land resources of the municipal formation ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes the state of land resources in the Russian Federation, the Republic of Bashkortostan; The structure of lands in state and municipal ownership is determined; The main directions with the emergence of management of land problems of the municipality are identified.
Keywords: landresources; municipality; management; property; land